The Role of Transformational Leadership in Enhancing Teacher Performance in Islamic-Based Schools - Diyan Firmansyah; Ma’rivarul Lativah; Marya Ulfa; Nirva Diana; Eti Hadiati; MHM. Majid (Postgraduate Program Magister Pendidikan Agama Islam, 2026)
This study aims to examine the role of principals’ transformational leadership in enhancing teacher performance in Islamic-based schools through a systematic literature review approach. The findings indicate that transformational leadership has a significant and positive influence on teacher performance, particularly in terms of motivation, professionalism, work discipline, instructional quality, and organizational commitment. Among the leadership dimensions, inspirational motivation and individualized consideration emerge as the most dominant factors contributing to improved teacher performance, while organizational culture, job satisfaction, and professional development serve as key mediating variables that strengthen leadership effectiveness in Islamic educational contexts. This study implies that leadership development programs and educational policies in Islamic schools should prioritize transformational leadership competencies integrated with ethical and spiritual values to foster sustainable improvements in teacher performance and overall school quality. Penelitian ini bertujuan untuk mengkaji peran kepemimpinan transformasional kepala sekolah dalam meningkatkan kinerja guru di sekolah berbasis Islam melalui pendekatan tinjauan literatur sistematis. Hasil kajian menunjukkan bahwa kepemimpinan transformasional memiliki pengaruh positif dan signifikan terhadap kinerja guru, khususnya dalam aspek motivasi, profesionalisme, disiplin kerja, kualitas pembelajaran, dan komitmen organisasi. Di antara dimensi kepemimpinan transformasional, motivasi inspirasional dan perhatian individual muncul sebagai faktor yang paling dominan dalam meningkatkan kinerja guru, sementara budaya organisasi, kepuasan kerja, dan pengembangan profesional berperan sebagai variabel mediasi yang memperkuat efektivitas kepemimpinan dalam konteks pendidikan Islam. Penelitian ini mengimplikasikan bahwa program pengembangan kepemimpinan dan kebijakan pendidikan di sekolah Islam perlu memprioritaskan kompetensi kepemimpinan transformasional yang terintegrasi dengan nilai-nilai etika dan spiritual guna mendorong peningkatan kinerja guru dan kualitas sekolah secara berkelanjutan.